2006
DOI: 10.1161/01.str.0000206142.03677.c2
|View full text |Cite
|
Sign up to set email alerts
|

Angioplasty for Symptomatic Intracranial Stenosis

Abstract: Background and Purpose-Medical treatment of symptomatic intracranial stenosis carries a high risk of stroke. This study was done to evaluate the clinical and angiographic outcomes after intracranial angioplasty for this disease. Methods-A total of 120 patients with 124 intracranial stenoses were treated by primary angioplasty. All patients had neurologic symptoms (stroke or transient ischemic attack) attributable to intracranial stenoses Ն50%. Angiograms were evaluated before and after angioplasty for the degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
154
0
6

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(164 citation statements)
references
References 22 publications
3
154
0
6
Order By: Relevance
“…Approximately 10% of our patients experienced complications after the initial PTA/stent treatment for intracranial stenotic disease; this complication rate agrees with earlier reports. 6,14,17,18,20) An important factor underlying the development of complications was distal embolism during the procedures. Our long-term outcomes were satisfactory and, compared to others, 1,4,10) the re-stenosis rate in our series was low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 10% of our patients experienced complications after the initial PTA/stent treatment for intracranial stenotic disease; this complication rate agrees with earlier reports. 6,14,17,18,20) An important factor underlying the development of complications was distal embolism during the procedures. Our long-term outcomes were satisfactory and, compared to others, 1,4,10) the re-stenosis rate in our series was low.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous transluminal angioplasty (PTA) for intracranial stenotic disease was introduced in the 1980s, 14) followed by combined stent placement in the 1990s. 8,22) PTA is used to treat stenotic lesions of the intracranial artery, but is associated with complications such as elastic recoil, acute obstruction, plaque embolization, arterial dissection, and occlusion of the perforating artery.…”
Section: Introductionmentioning
confidence: 99%
“…Similar data were obtained in other angiography studies, which showed high-grade intracranial lesions in 35%-49% of cases. 1,7,13 In our study, we did investigate 2 ICA segments in detail, especially those in which the MR imaging artifact problem frequently occurs and in which angioplasty may not be complicated by an extremely tortuous arterial course. 19 Tandem stenosis of the ICA is of special interest in patients undergoing surgical ICA revascularization or stent placement.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Endovascular treatments involving angioplasty for 50%-99% ICA stenosis have also been applied but are considered experimental approaches in need of validation by controlled studies. [11][12][13] Because the course of intracranial ICA is complicated due to its tortuosity and variability, classification of this portion of the vessel may differ between authors, [14][15][16] in turn complicating interpretation of the data. The "gold standard" used to assess the intracranial ICA remains digital subtraction angiography (DSA).…”
mentioning
confidence: 99%
“…10 The use of conservative angioplasty and the Wingspan stent (Boston Scientific, Natick, Massachusetts) as a self-expanding nitinol stent specifically developed for intracranial atherosclerotic stenosis has brought down the periprocedural stroke or death rate from 9.5% (95% CI, 7.0%-12.0%) in a meta-analysis to 4.5%. 11,12 The MCA is a common location of stenosis in the anterior circulation; it is more peripherally located and of a relatively smaller caliber compared with the other common locations of intracranial stenosis. It is hypothesized that intracranial atherosclerosis located at the MCA is technically more challenging for angioplasty and stent placement and is associated with a suboptimal treatment outcome.…”
mentioning
confidence: 99%